2015
DOI: 10.1111/1440-1681.12405
|View full text |Cite
|
Sign up to set email alerts
|

The role of Krüppel‐like factor 4 in transforming growth factor‐β–induced inflammatory and fibrotic responses in human proximal tubule cells

Abstract: Krüppel-like factor 4 (KLF4) is known to mitigate inflammation in several cell types. Using human proximal tubule cells, the present study aimed to investigate the role of KLF4 in regulating transforming growth factor (TGF)-β₁ induced inflammatory and fibrotic responses. Human kidney proximal tubular cells were exposed to high glucose, or TGF-β₁ and KLF4 expressions were determined. Cells were then transfected with empty vector or KLF4 and exposed to 2-ng/mL TGF-β₁ for up to 72 h. Inflammatory proteins (macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Our results suggest that KLF4 is down regulated in smooth muscle cells by hyperglycemia as well as in arteries from diabetic mice and patients. These results are consistent with earlier findings in other tissues including adipose tissue and kidney (Aktug et al, ; Hayashi et al, ; Liao et al, ; Mreich, Chen, Zaky, Pollock, & Saad, ) but in conflict with recent results in smooth muscle (Shyu, Cheng, & Wang, ; Xi, Wai, White, & Clemmons, ). The reason for these discrepancies is not known, but may be due to differences in diabetes models or the time point at which KLF4 expression is analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that KLF4 is down regulated in smooth muscle cells by hyperglycemia as well as in arteries from diabetic mice and patients. These results are consistent with earlier findings in other tissues including adipose tissue and kidney (Aktug et al, ; Hayashi et al, ; Liao et al, ; Mreich, Chen, Zaky, Pollock, & Saad, ) but in conflict with recent results in smooth muscle (Shyu, Cheng, & Wang, ; Xi, Wai, White, & Clemmons, ). The reason for these discrepancies is not known, but may be due to differences in diabetes models or the time point at which KLF4 expression is analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…Attenuation of proteinuria by renin-angiotensin blockage was found to be in part via KLF4 suppression (116). In contrast to the proinflammatory role of KLF4 in other systems, KLF4 was shown to reduce inflammation (triggered by TGF-β1) and fibrotic responses, in renal tubular cells during diabetic nephropathy (117). Also, it was recently shown that KLF4 is involved in the regulation of renal physiological functions and the progression of fibrosis (118).…”
Section: Physiological Functions In Tissues and Organsmentioning
confidence: 99%
“…In the diabetic kidney, the KLF4 mRNA level is remarkably reduced. In an animal model of diabetic nephropathy, KLF4 expression was significantly decreased in renal tubular cells (Mreich et al, 2015 ). Renal fibrosis is considered to be one of the major pathological changes that occur during the course of diabetic nephropathy (Arora and Singh, 2013 ).…”
Section: The Biological Characteristics Of Klf4mentioning
confidence: 99%